Fault Diagnosis of Wind Turbine Gearbox based on Signal Model and Order Analysis - Jiabin Tian; Yanyan Nie; Xiaoxu Chen; Hao Xu; Fangyi Li; Liming Wang (Jixie chuandong)
Aiming at the phenomenon of spectrum ambiguity caused by traditional spectrum analysis method under non-stationary load， a signal model and order analysis method is used to study the fault diagnosis of the wind turbine gearbox. The vibration signal model of high speed stage of gearbox under non-stationary load is established， and the structure of time spectrum and order spectrum is derived. The order analysis method is used to analyze the order spectrum of vibration signal and extract gear fault feature. Finally， the real wind field gearbox data is analyzed， and the fault in gearbox is identified accurately.